'We are at war': Continuity and rupture in French anti-terrorist discourse. (June 2019) - Fragnon, Julien
This article analyses the circulation of the word 'war' in French anti-terrorist discourse since the 1980s. Although its use was apparent well before the attacks carried out in 2015, it experienced such a rise in frequency that it formed a discursive rupture. Its usage seeks to intensify the intentions traditionally evoked by anti-terrorist discourse by calling attention to amplification in the situation, while also seeking to justify a strategy based on exceptional circumstances.